Application of Green Marketing and Brand Awareness in Increasing Purchasing Decisions at Starbucks Medan Petisah - Roberto Lie; Irvan Rolyesh Situmorang; Jessa B. Labitad; Shiny Rose N. Narit (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This study aims to determine whether Green Marketing and Brand Awareness have a significant effect on Purchasing Decisions at Starbucks Medan Petisah. This study uses quantitative data methods and the data source is primary data. The population in this study were 50,570 consumers of Starbucks Medan Petisah obtained from the population of Starbucks Medan Petisah during 2023. The sample of this study was calculated using the Slovin formula so that 100 respondents were obtained and using simple random sampling data collection techniques. Data analysis and testing consists of validity test, reliability test, descriptive statistical test, classical assumption test, multiple regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and coefficient of determination test. The results showed that Green Marketing has a partially significant effect on Purchasing Decisions at Starbucks Medan Petisah. Brand Awareness has a partially significant effect on Purchasing Decisions at Starbucks Medan Petisah. Green Marketing and Brand Awareness simultaneously have a significant effect on Purchasing Decisions at Starbucks Medan Petisah with an Fcount value of 145.208> Ftable 3.09 and a regression coefficient value of 75%.